An Enhanced Solar Hybrid Brayton and Rankine Cycles with Integrated Magnetohydrodynamic Conversion System for Electrical Power Generation - Ayokunle Oluwaseun Ayeleso; Atanda Kamoru Raji (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
In many developing countries,the use of conventional power plants to generate electricity is not meeting the increasing demands. Therefore, it has become important to find sustainable alternatives. In the present study, a solar hybrid combined cycle power plant consisting of a solar thermal plant, large-scale gas and steam turbines, and a magnetohydrodynamic generator has been investigated under oxy-fuel combustion. The performance analysis of this system under fuel pressure rate varying from 10 to 25 bar was conducted using Cycle Tempo software. The analysis of the gas and steam combined cycle shows that the net powers and the net efficiencies obtained ranged from 98 MWe to 134 MWe and 30.5% to 40%, respectively. In addition, the integration of the magnetohydrodynamic generator to the combined cycle led to an increase in the overall power from 169 MWe to 205 MWe. Moreover, it is seen that the fuel mass rate (2.81 kg/s) obtained in the gas turbine system under oxy-fuel combustion is significantly reduced when compared to conventional systems. The incorporation of solar energy and oxy-fuel combustion in the gas turbine system has increased the combustor inlet and outlet temperature and reduced the fuel consumption. From these observations, the solar hybrid system proposed in this study does not only generates electric power but also reduce the turbine exhaust fumes and CO2 emissions, which is a key factor in minimizing environment pollution.